Numerical and experimental investigation of wave dynamics on a land-fixed OWC device. (15th November 2016) - Ning, De-Zhi; Wang, Rong-Quan; Gou, Ying; Zhao, Ming; Teng, Bin
Abstract: An Oscillating Water Column (OWC) Wave Energy Converter (WEC) is a device that converts the energy of ocean waves to electrical energy. When an OWC is designed, both its energy efficiency and the wave loads on it should be considered. Most attentions have been paid to the energy efficiency of an OWC device in the past several decades. In the present study, the fully nonlinear numerical wave model developed by Ning et al. (2015) [1] is extended to simulate the dynamic wave forces on the land-fixed OWC device by using the acceleration potential method, and the experimental tests are also carried out. The comparisons between numerical results and experimental data are performed. Then the effects of wave conditions and chamber geometry on the wave force on the front wall of the chamber are investigated. The results indicate that the total wave force decreases with the increase of the wavelength and increases with the increase of the incident wave height. The wave force is also strongly influenced by the opening ratio, i.e., in the low-frequency region, the larger the opening ratio, the smaller the wave force and it shows an opposite tendency in the high-frequency region. Highlights: The wave dynamics on a land-fixed OWC device is numerically and experimentally studied. The largest wave pressure occurs on the outside of the front wall on the free surface under the action of the wave crest. The total horizontal wave load on the front wall decreases with the increase of the wavelength. The opening ratio greatly influences the wave force on the front wall.